Maternal knowledge and adherence to iron-rich diet: A multicenter cross-sectional study - Jafaru Yahaya; Yusuf Abdulrahman Bashir; Aisha Abdullahi Magaji; Umar Faruk Magaji; Aliyu Abdullahi Turaki; Ufuoma Bigila Shemishere; Muhammad Shafiu AbdulRauf; Fatima Musa; Daniel Anyebe (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The high physiological demand for an iron in pregnancy depend on both the quantity and quality of diet that a woman takes. Inadequate intake of dietary iron, interference with iron absorption, and or increased demands during pregnancy can lead to iron deficiency anemia. Purpose: To assess the relationship between maternal knowledge and adherence to an iron-rich diet. Method: The study employed cross-sectional design, and the population of the study was pregnant women attending antenatal clinic in three tertiary hospitals of Kebbi State, Nigeria. Data were collected using 20 items researcher-constructed self-administered questionnaire generated from reviewed literatures and based on objectives of the study. Results were presented using frequency distribution and simple percentages. Chi-square statistical tool was used for testing the hypotheses using SPSS Version 27. Results: These data indicate that 12.7% of respondents had a low level of adherence with an iron-rich diet. However, only 39.0% were found to have a high level of adherence. It was revealed that there was a significant relationship between the demographic variables assessed and adherence with an iron-rich diet, p<0.01 except for the age group with a p value<0.05. Conclusion: There was a significant relationship between the demographic variables assessed and adherence to iron-rich diet in all variables. Suggestions: There is a need for further efforts to educate pregnant women about iron-rich diet with an emphasis on foods that help the body absorb and use iron and foods that reduce iron absorption. Educating pregnant women about all aspects of pregnancy including health promotion and prevention of complications during pregnancy is primarily the role of midwives.